Inhibitory effect of local Honey on Bacteria in culture media and in laboratory animals: Ali,A.Abed Al-abbas Saffaa,A.A Abbas,H.N.Al-saeed - Al-abbas, Ali A.Abed (The Iraqi Journal of Veterinary Medicine, 2010)
This study was carried out at the animal station agriculture and the foodtechnology research center of Iraqi ministry of science & Technology. In a study todetermine the inhibitory effect of honey in the local growth of some pathogenicbacteria in growth media (In vivo) and in laboratory animals (Invitro) was used fourtypes of bacteria brought from the Central Health Laboratory - Baghdad,Escherichia coli , Streptococcus pneumoniae , Staphylococcus aureus , Streptococcuspyogenus and Pasteurella hemolytica, and their biochemical characteristics were reexamined.The study deals with studying the effect of local honey in the inhibition ofthe growth of these bacteria on environmental Nutrient Agar (Invitro) to measurethe diameter of zone inhibition after incubator the culture media for a period of24-48 hours, as for the study of the effect of honey in laboratory animals(mouse Invivo) 12 groups of local mice were used, in addition to four mice of each controlgroup. Each group is given (cfu / ml 104 ) of specific bacteria once and then it isgiven Diluted honey of different concentrations (5%,10%,20%)with drinking waterfor one week to all groups except the control group.The study showed a differentdegree of inhibition of honey depending on the type of bacteria and whether thebacteria is negative or positive of the dye gram and the inhibitory effect of thehoney in the nutrient broth increased according to the concentration of honey.The results in animals laboratory differed sometimes depending on the type ofbacteria, this indicates that local honey is good in efficiency in reducing bacterialgrowth which might qualify for use as a treatment supporter with drugs and this iswhat must be expanded in future studies.